Immune Checkpoint Inhibitors: A Promising Choice for Endometrial Cancer Patients? - Musacchio, Lucia (J Clin Med, 2020)
Although around 80% of endometrial cancers are diagnosed at early stages and present with a 5-year survival rate exceeding 95%, patients with advanced and recurrent disease show a poor prognosis and low response rates to standard chemotherapy. In the era of targeted therapy, the great advances in the understanding of programmed death-ligand 1 (PD-L1) upregulation in cancer cells, which is responsible for tumor immune escape, have contributed to the increasing interest in immune checkpoint inhibitors as a promising strategy for the treatment of several refractory solid malignancies, including endometrial cancer. Several clinical trials have investigated the efficacy and safety of immune checkpoint inhibitors in endometrial cancer, which already led to the approval of the anti-programmed cell death protein 1 (anti-PD-1) antibody pembrolizumab as a satisfactory alternative for selected patients with unresectable or metastatic disease. As the future of cancer treatment will probably rely on combination therapy strategies, currently, innovative ongoing trials are exploring the potential role of immune checkpoint inhibitors associated with chemotherapy, radiotherapy, and other targeted therapies. Moreover, further research is warranted to discover new specific biomarkers that can accurately predict the response to immunotherapy.